BUKAN SEKADAR MENGHAFAL SEMALAM:KAJIAN LITERATUR TENTANG MODEL PEMBELAJARANUNTUK RETENSI MEMORI JANGKA PANJANG - Nur Mufidah; Harun Al Rasyid (CV. ADIBA AISHA AMIRA, 2026)
Cramming massing all study into a single pre-exam session remains the default learning strategy across educational levels, despite converging evidence that it fails to build durable long-term memory. This narrative literature review identifies, analyzes, and synthesizes evidence-based learning models that reliably improve long-term retention, while tracing their alignment with Islamic educational principles. The review searched five databases: Scopus, ERIC, PsycINFO, Google Scholar, and Sinta. An initial yield of 847 sources was screened systematically, producing 34 final sources 26 internationally indexed articles (Scopus/WoS), 6 nationally accredited Indonesian journal articles (Sinta), and 2 official international data sources spanning 2002–2024, with explicit exceptions for foundational theoretical works. Six empirically supported models were identified: spaced repetition, retrieval practice, elaborative interrogation, interleaved practice, meaningful learning, and metacognitive learning. All six not only align with modern cognitive neuroscience but find strong precedent in Islamic educational tradition from authentic hadith on Qur'anic muraja'ah to the Prophet's ﷺ dialogue-based pedagogy. The review further produces an original integrative framework, REIM (Retrieval-Elaboration-Interleaving-Metacognition), offering a hierarchical implementation sequence within the tarbiyah islamiyah context.